2017
DOI: 10.5194/bg-2017-456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large to submesoscale surface circulation and its implications on biogeochemical/biological horizontal distributions during the OUTPACE cruise (SouthWest Pacific)

Abstract: Abstract. The patterns of the large-scale, meso-and submesoscale surface circulation on biogeochemical and biological distributions are examined in the Western Tropical South Pacific (WTSP) in the context of the OUTPACE cruise (Feb-April 2015).Multi-disciplinary original in situ observations were achieved along a zonal transect through the WTSP and their analysis was coupled with satellite data. The use of Lagrangian diagnostics allows for the identification of water mass pathways, mesoscale structures, and su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
4
5
0
Order By: Relevance
“…Their trajectories showed a turbulent surface flow (Figs. S7b, d) and the absence of a main stream, in agreement with Rousselet et al (2018).…”
Section: Physical Features Of the Study Areasupporting
confidence: 82%
See 1 more Smart Citation
“…Their trajectories showed a turbulent surface flow (Figs. S7b, d) and the absence of a main stream, in agreement with Rousselet et al (2018).…”
Section: Physical Features Of the Study Areasupporting
confidence: 82%
“…In the center of the Lau Basin (> 100 km downstream of the arc), these trajectories showed the presence of a southwest flow regardless of the depth (Figs.S7a, c and S8a, c). Numerical simulations agree with these observations asRousselet et al (2018) showed a general transport west of 170 °W as follows: surface waters enter from the northeast via the SEC and propagate southwestward towards the various archipelagos present in the WTSP Ocean. Lagrangian velocities measured along the trajectories are about five times higher at the surface (SVP drifters: 0-15 m) than at depth (Argo floats: 1000-1500 m) in the Lau Basin.…”
supporting
confidence: 69%
“…(a) Chl observed at the peak of the LD‐B bloom. Reproducing previous results (de Verneil et al, ; Rousselet et al, ), gray lines display 60‐day backward Lagrangian trajectories initialized at high‐Chl patches near LD‐B (Chl > 0.75 mg m −3 , black crosses). (b) Chl and surface currents observed during the previous 30 days, providing information on water mass pathway and bloom generation (note the different color bar).…”
Section: Introductionsupporting
confidence: 63%
“…This produces an Eulerian perspective, and this methodology is employed by definition at permanent mooring platforms. Set geographic locations are also often used to define time series or recurrent sampling locations, for example stations ALOHA, BATS, CalCOFI, DYFAMED, and PAPA (Karl and Lukas, 1996;Schroeder and Stommel, 1969;Steinberg et al, 2001;Bograd et al, 2003;Marty et al, 2002;Freeland, 2007). These sites can be combined into worldwide networks and initiatives such as OceanSITES (Send et al, 2010).…”
Section: Introductionmentioning
confidence: 99%